Quality Control of Herbal Medicines (The East and Central African Journal of Pharmaceutical Sciences, 2018)
The use of traditional and herbal medicines is gaining recognition globally. To safeguard the patient, there are legitimate demands that all medicines be safe, efficacious and of good quality. The required parameters for their quality evaluation include assessment for inorganic matter (dust), absence of adulteration, microbial load, identification and profile of contents and where possible quantitation of the active compound or marker compounds. Also of importance are heavy metals, pesticides and product stability. The mixture of portions of herbs in traditional medicines complicates the quality control tests of these preparations. The content profile becomes difficult to replicate from batch to batch, while quantification of the active compound(s) in such multi-component products would require prior processing to isolate and identify the chemical compounds
Keywords: Herbal medicines quality control